Implementasi Pendidikan Karakter di Era Disrupsi Digital: Studi Kasus di SD Nasima - Lulu’ Arifatun Munasiroh; Eka Titi Andaryani; Joko Sutarto; Indriana Eko Armaidi (Indo Publishing, 2026)
This study aims to examine the dynamics of character education in addressing digital technology disruption in formal education, particularly at SD Nasima. The research employs a descriptive qualitative approach to explore how digital technology is integrated into the learning process while maintaining the implementation of character education. Data were collected through observation, interviews, and documentation involving school principals, teachers, and students. The findings reveal that digital technology has been effectively utilized to enhance student engagement, motivation, and learning experiences through various digital platforms and interactive media. At the same time, character education remains a central focus, implemented through classroom activities, school culture, and daily habituation. However, several challenges were identified, including excessive gadget use, reduced face-to-face social interaction, and disparities in students’ digital literacy levels. To address these challenges, the school has implemented strategies such as strengthening digital literacy, regulating technology use, integrating character values into digital learning, and fostering collaboration with parents. The study concludes that character education in the digital era can be effectively sustained through the balanced integration of technology, strong teacher competence, and active collaboration between schools and families.